Cross-Cultural Comparison of Burnout, Insomnia and Turnover Intention Among Nurses in Eastern and Western Cultures During the COVID-19 Pandemic: Protective and Risk Factors - Eveline Frey; Yuen-Yu Chong; Wai-Tong Chien; Andrew T. Gloster (Nursing Reports, 2025)
Background/Objectives: The COVID-19 pandemic has adversely impacted the mental health of nurses worldwide. Nurse burnout results from chronic workplace stress and is characterized by exhaustion, negative or cynical feelings about work, and a diminished sense of accomplishment. This can lead to turnover intention. Therefore, psychological capacities, such as psychological flexibility, that could help nurses regulate and minimize the impact should be studied. This study aimed to compare burnout, insomnia and turnover intention among nurses from an Eastern and Western cultural context and to investigate the role of psychological flexibility as a protective factor against mental health and related problems such as insomnia and turnover intention. Methods: Nurses from Hong Kong (n = 158) and Switzerland (n = 294) involved in patient care during the COVID-19 pandemic participated in an online mental health survey. Results: We observed high levels of burnout, subthreshold insomnia and turnover intention in nurses from both Switzerland and Hong Kong, with higher burnout rates among Hong Kong nurses and higher turnover intentions among nurses from Switzerland, and that psychological flexibility is a crucial factor that may protect nurses from burnout and insomnia. Conclusions: The nurses from both regions involved in patient care one year after the onset of the pandemic suffered from poor mental health. Psychological flexibility was identified as a critical factor in improving nurses’ mental health. The results of this study should be incorporated into health promotions for nursing professionals and help develop specific and effective interventions for practical nursing application.